Protein Kinase Inhibitors in Rheumatology (2014)
ABSTRACT: Protein kinases have multiple roles in cell biology, many of which are deeply involved in inflammation and immunity. There are currently many treatment options for patients with autoimmune disease, but none that is completely effective. Protein kinase inhibitors are becoming one of the most promising therapeutic groups, not only for the treatment of disease, but for further developing our understanding of different pathologies. The purpose of this paper is to give an introduction to both protein kinases and their inhibitors, with their implications in the management of autoimmune diseases.